First part: Storage unsaturated water in a soil profile - Chavarría-Vidal, Adrián (2021)
A foundation for the correct and efficient application and use of the water resource in agricultural production systems is to know the state of humidity in which the soil is found since the amount to be applied must be the same as the amount consumed in the soil system - plant through evapotranspiration. This state of humidity must be estimated as close as possible to reality and for this, the soil profile should be taken at a depth to which it adapts best to the crop (s) present. Normally the appropriate depth refers to the depth of the roots of the plants and the form of estimation can be given in several ways and one of them is by means of the volumetric humidity which, can be estimated directly as indirectly (as an example we can mention calibrated sensors). However, with the information obtained from the field, the respective total estimate must be made and will depend on the methodology used with respect to the defined depth, the number of samples and the distance between the samples, which; The latter are recommended to be the same length. Therefore, the main objective of this article is to present different options for managing the information obtained from the field to estimate unsaturated water contents in a soil profile, compare them in their estimates for better decision making.